Spousal cooperation and marriage norms - Afzal, Uzma (2021)
This thesis presents three studies within the fields of behavioural and experimental economics. Chapter 1 introduces the thesis and provides an overview of the research themes and methods and reports the main research findings. Chapter 2 reports a lab-in-the-field experiment that investigates the systematic heterogeneity in cooperative decision-making across spouses in arranged and love matched marriages in Pakistan. We find that spouses in love matched marriages are significantly more likely to be unconditionally cooperative. Chapter 3 reports the second round of the field experiments and examines (1) whether the finding from Chapter 2 replicates, (2) whether it generalizes to couples living in more remote villages and, (3) whether the observed difference in unconditional cooperativeness between spouses in love versus arranged marriages can be explained by the selection of unconditionally cooperative people into love marriages. We find that in villages close to the city love matched spouses are significantly more likely to be unconditionally cooperative. However, as distance from the city increases, the love matched effect declines. We conjecture that this is owing to less tolerance for love marriages in more remote areas. Chapter 4 investigates the content and strength of the social norms and personal normative beliefs relating to marriage arrangements. It also examines the second-order social norms and personal normative beliefs on marriage. We investigate the social norms by implementing incentivised coordination games and the personal normative beliefs using unincentivized surveys. We find that there is indeed a social norm against love matched marriages and that this norm is stronger in more remote villages. However, the subjects’ personal normative beliefs often diverged from the social norm. Our results also confirm that men are extended greater autonomy to deviate from the arranged marriage norm compared to women. We find no substantive evidence supporting the existence of a second-order norm. Chapter 6 summarises the findings and concludes.